Females have Lower Knee Strength and Vertical Ground Reaction Forces During Landing than Males Following Anterior Cruciate Ligament Reconstruction at the Time of Return to Sport - Zachary B. Sullivan; Barrie S. Sugarman; Mallory S. Faherty; Carrie Killelea; Dean C. Taylor; Daniel Le; Alison P. Toth; Jonathan C. Riboh; Lee H. Diehl; Jocelyn R. Wittstein; Annunziato Amendola; Timothy C. Sell (International Journal of Sports Physical Therapy)
# Purpose